Визначення індексу керногана судин селезінки представників птахів і ссавців - Дунаєвська, Оксана; Dunaіevska, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2017)
На основі морфометричних досліджень артерій білої пульпи розраховано індекс Керногана. Найбільше значення ІК центральної артерії лімфоїдного вузлика й періартеріальних лімфоїдних піхв білої пульпи селезінки визначено в курки (1,61±0,36 і 3,19±0,41 відповідно), найменше – у коня (0,70±0,27 і 1,01±0,31) Kernohan’ index allows evaluating the functional state of the vessels and includes the parameters that determine immunomorphology spleen. The white pulp is responsible for the immune response that is why appropriate to calculate the index of the vessels of this structure. Kernohan` index is calculated on the basis of morphometric studies of the arteries (wall thickness, internal diameter) components of the white pulp. The highest value of Kernohan` index in the central artery of lymphoid follicles and lymphoid sheaths near the vessels of the white pulp of the spleen was identified in chicken (1,61 ± 0,36 3,19 ± 0,41 respectively), the lowest – in the horse (0,70 ± 0,27 and 1, 01 ± 0,31 respectively). It is found that the Kernohan’ index of central artery lymphoid` follicle more than 1,14 times than the arteries in lymphoid sheaths near the vessels in the rabbit. The value of the Kernohan’ index in artery lymphoid sheaths near the vessels more than the lymphoid follicle in 1,35 times (dove); in 1,44 times (pig, horse), in 1,47 times (cattle); 1,73 times (sheep); 1,98 times (chicken).
The Kernohan’ Index Definition in Vessels of the Spleen of Birds and Mammals
Keywords: селезінка; артерії білої пульпи; індекс Керногана; spleen; arteries of white pulp; Kernohan` index